Ultra-low-molecular-weight heparins: Precise structural features impacting specific anticoagulant activities - Lima, Marcelo A.; Viskov, Christian; Herman, Frederic; Gray, Angel L.; de Farias, Eduardo H. C.; Cavalheiro, Renan P.; Sassaki, Guilherme L.; Hoppensteadt, Debra P.; Fareed, Fareed P.; Nader, Helena B. (Thrombosis and Haemostasis, 2013)
Ultra-low-molecular-weight heparins (ULMWHs) with better efficacy and safety ratios are under development; however, there are few structural data available. The main structural features and molecular weight of ULMWHs were studied and compared to enoxaparin. Their monosaccharide composition and average molecular weights were determined and preparations studied by nuclear magnetic resonance spectroscopy, scanning ultraviolet spectroscopy, circular dichroism and gel permeation chromatography. In general, ULMWHs presented higher 3-O-sulphated glucosamine and unsaturated uronic acid residues, the latter being comparable with their higher degree of depolymerisation. The analysis showed that ULMWHs are structurally related to LMWHs; however, their monosaccharide/oligosaccharide compositions and average molecular weights differed considerably explaining their different anticoagulant activities. The results relate structural features to activity, assisting the development of new and improved therapeutic agents, based on depolymerised heparin, for the prophylaxis and treatment of thrombotic disorders.
Keywords: Heparin; enoxaparin; molecular weight; spectroscopy; anticoagulant activity